Health-related quality of life of teen/adult patients with cystic fibrosis in the Republic of North Macedonia - Nakov Z., Acevski S., Velkoska V., Naceva Fushtik S., Nakov N., Tonikj Ribarska J., Trajkovikj Jolevska S. (My University, 2021)
The present study investigates the Health-related quality of life of teen/adults patients with cystic fibrosis in the Republic of N. Macedonia for the first time. The main objective was to describe the health-related quality of life status of these patients with cystic fibrosis and the second objective was to investigate the connection of the current medical treatment with the analysed parameters. The survey was conducted on 31 patients by using the Cystic Fibrosis Questionnaire Revised for Health-related quality of live measurement and questions for current medical treatment. All patients scored their digestive condition with the highest score, while the lower score was reported for social activity. The gender, the nationality and the educational level of the patients with Cystic Fibrosis had no significant impact on their perception of Health-Related Quality of Live. The highest score for digestive condition was in positive correlation with the fact that all patients continuously used enzyme therapy. Patients who practiced physical therapy and physical activities reported high scores for physical conditions and body images. This finding point out that patient with Cystic Fibrosis should be encouraged to practice physical activity more often. The lowest scores for life activities and treatment burden shows that this medical condition has a negative impact on the patients’ self-perception and in the execution of their daily activities.
Keywords: cystic fibrosis, Health-Related Quality of Live, digest, daily activities